Directly Measured Denitrification Reveals Oyster Aquaculture and Restored Oyster Reefs Remove Nitrogen at Comparable High Rates - Humphries, Austin T.; Ayvazian, Suzanne G.; Carey, Joanna C.; Hancock, Boze T.; Grabbert, Sinead; Cobb, Donald; Strobel, Charles J.; Fulweiler, Robinson W. (Frontiers in Marine Science, 2016)
Coastal systems are increasingly impacted by over-enrichment of nutrients, which has cascading effects for ecosystem functioning. Oyster restoration and aquaculture are both hypothesized to mitigate excessive nitrogen (N) loads via benthic denitrification. The degree to which these management activities perform similar functions for removing N, however, has not been extensively examined in New England, a place where nutrient runoff is high and increasing oyster (Crassostrea virginica) restoration and aquaculture activity is taking place. Here, we use a novel in situ methodology to directly measure net N2 and O2 fluxes across the sediment-water interface in a shallow (~1 m) coastal pond in southern Rhode Island. We collected data seasonally during 2013 and 2014 at restored oyster reefs, oyster aquaculture, oyster cultch (shell), and bare sediment. Restored oyster reefs and aquaculture had the highest mean (± SE) denitrification rates, 581.9 (± 164.2) and 346 (± 168.6) μmol N2-N m-2 h-1, respectively, and are among the highest recorded for oyster-dominated environments. Denitrification rates at sites with oyster cultch were 60.9 (± 44.3) μmol N2-N m-2 h-1, which is substantially less than the sites with active oysters but still more than 50% higher than denitrification rates measured in bare sediment (24.4 ± 10.1 μmol N2-N m-2 h-1). The increase in denitrification rates at treatments, however, varied by season and the greatest rates for restored reefs were in the fall. Overall, the greatest aggregate denitrification rates occurred in the fall. Sediment oxygen demand (SOD) followed similar patterns but with greater overall rates in the summer, and displayed a strong linear relationship with denitrification (R2 = 0.9273). Our results demonstrate that habitats associated with live oysters have higher net denitrification rates and that oyster reef restoration and oyster aquaculture may provide similar benefits to the ecosystem in terms of N removal. However, gas fluxes may also be affected where three-dimensional structure is introduced via oyster shell cultch and this appears to be seasonally-dependent. These data will be important for managers as they incorporate oysters into nutrient reduction strategies and consider system-level trade-offs in services provided by oyster reef restoration and aquaculture activities.